2022
DOI: 10.3389/fpls.2022.1033192
|View full text |Cite
|
Sign up to set email alerts
|

Two-component system ArcBA modulates cell motility and biofilm formation in Dickeya oryzae

Abstract: Phytopathogen Dickeya oryzae is a causal agent of rice foot rot disease and the pathogen has an array of virulence factors, such as phytotoxin zeamines, plant cell wall degrading enzymes, cell motility, and biofilms, collectively contributing to the bacterial pathogenesis. In this study, through deletion analysis of predicted regulatory genes in D. oryzae EC1, we identified a two-component system associated with the regulation of bacterial virulence. The two-component system contains a histidine kinase ArcB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…In A. baumannii, OmpR-EnvZ was found to regulate motility [18], and the hybrid sensor kinase A1S_2811 was reported to regulate surface motility and biofilm formation via the chaperone/usher pili-associated csuA/ABCDE operon and the AbaI-dependent quorum-sensing pathway-associated A1S_0112-0119 operon [10]. In other bacteria, such as avian pathogenic E. coli, KdpD/KdpE contributed to the expression of some flagella-related genes involved with flagella formation and motility [35], while in Dickeya oryzae, ArcBA was found to modulate cell motility and biofilm formation [36]. Interestingly, the recent research in A. baumannii strain MAR002 has shown that virulence is decreased when impairments in surface-associated motility occur, but not when twitching motility is affected [37].…”
Section: Discussionmentioning
confidence: 99%
“…In A. baumannii, OmpR-EnvZ was found to regulate motility [18], and the hybrid sensor kinase A1S_2811 was reported to regulate surface motility and biofilm formation via the chaperone/usher pili-associated csuA/ABCDE operon and the AbaI-dependent quorum-sensing pathway-associated A1S_0112-0119 operon [10]. In other bacteria, such as avian pathogenic E. coli, KdpD/KdpE contributed to the expression of some flagella-related genes involved with flagella formation and motility [35], while in Dickeya oryzae, ArcBA was found to modulate cell motility and biofilm formation [36]. Interestingly, the recent research in A. baumannii strain MAR002 has shown that virulence is decreased when impairments in surface-associated motility occur, but not when twitching motility is affected [37].…”
Section: Discussionmentioning
confidence: 99%